Sphingobacterium multivorum: An Atypical Bacterium in an Atypical Place - Pernas-Pardavila, Hadrián (Eur J Case Rep Intern Med, 2019)
We present the case of a 75-year-old woman admitted to hospital because of an infected pressure ulcer. Cultures revealed that the responsible bacterium was Sphingobacterium multivorum, which was successfully eradicated with ciprofloxacin. Over the last few years, there have been reports of new cases of infection caused by bacteria previously not thought to be harmful to humans, like S. multivorum. Previous cases were reported mostly in immunosuppressed patients and the present report is, to our knowledge, the first describing a pressure ulcer infected by this bacterium. LEARNING POINTS: Bacteria previously not thought to be harmful to humans can cause disease. Sphingobacterium multivorum should be considered a potential cause of pressure ulcer infection. As S. multivorum may be resistant to many antibiotics, complete susceptibility testing should be mandatory.